Evaluation of seismic torsional response of ductile RC buildings with soft first story. (February 2021) - Hareen, CH.B.V.; Mohan, S.C.
Abstract: This study investigates the inelastic torsional response of plan asymmetric ductile RC buildings with a soft first story. The buildings of Rectangular, L, T, and U plan shapes are considered for the study. Force-based fiber beam-column elements are modeled for the inelastic response prediction of the buildings. Masonry infill walls are uniformly distributed in the plan and considered for the evaluation of torsional response. The pushover methods, Extended N2 and Extended Capacity Spectrum Method – FEMA 440 are adopted to estimate the inelastic torsional response. Bi-directional nonlinear time history analysis is carried out on the buildings considering near-field and far-field ground motions. Story drift ratio and curvature demand-capacity (D/C) ratio of columns are reported at the stiff, flexible side of buildings. The torsional response of infill wall buildings is compared with that of bare frame buildings. It was observed that the torsionally irregular ductile buildings with soft first story exhibit higher seismic demand on the flexible side corner columns. Infill wall interaction amplifies the torsional response at the bottom story, causing an increase in displacements higher at the flexible side and moderate near the stiff side. This study concludes that the flexible side corner column in plan asymmetric building with a soft first story can be conservatively designed for 1.5 times the design forces obtained from the analysis. This conservative design ensures stable energy dissipation in the corner column under load reversals, without significant strength reduction under higher excitation levels. The designer shall properly distribute lateral load resisting elements in a plan to prevent premature failure of the columns located internally and close to the initial center of rigidity. The designer can avoid the collapse of columns located internally in the buildings with stiff peripheral frames by designing for forces 1.5 times higher than obtained.